'Good' Parenting Practices: How Important are Poverty, Education and Time Pressure?. (February 2016) - Dermott, Esther; Pomati, Marco
This article examines how parenting practices popularly classed as 'good' are related to poverty, education and time pressure. Using the 2012 UK Poverty and Social Exclusion (PSE) survey we argue that parenting practices such as reading, playing games and eating meals together are not absent among those who are less well educated, have lower incomes or are more deprived of socially accepted necessities: therefore, political claims of widespread 'poor parenting' are misplaced. Further, we suggest that the dominant trope of poor people being poor at parenting may arise because the activities of the most educationally advantaged parents – who do look different to the majority – are accepted as the benchmark against whom others are assessed. This leads us to suggest that the renewed interest in sociological research on elites should be extended to family life in order that the exceptionality of the most privileged is recognised and analysed.